Discovery of a novel azetidine scaffold for colony stimulating factor-1 receptor (CSF-1R) Type II inhibitors by the use of docking models. Issue 1 (1st January 2019) - Ikegashira, Kazutaka; Ikenogami, Taku; Yamasaki, Takayuki; Hase, Yasunori; Yamaguchi, Takayuki; Inagaki, Koji; Doi, Satoki; Adachi, Tsuyoshi; Koga, Yoshihisa; Hashimoto, Hiromasa
Graphical abstract: Highlights: A novel series of azetidine scaffold were identified as colony stimulating factor-1 receptor (CSF-1R) Type II inhibitors. Compound4a showed high CSF-1R inhibitory activity (IC50 = 9.1 nM). A co-crystal structure of an azetidine compound with CSF-1R was obtained. Abstract: We report the discovery of a novel azetidine scaffold for colony stimulating factor-1 receptor (CSF-1R) Type II inhibitors by using a structure-based drug design (SBDD) based on a docking model. The work leads to the representative compound4 a with high CSF-1R inhibitory activity (IC50 = 9.1 nM). The obtained crystal structure of an azetidine compound with CSF-1R, which matched our predicted docking model, demonstrates that the azetidine compounds bind to the DFG-out conformation of the protein as a Type II inhibitor.